Incidence, Antibiogram, and Comorbid Conditions of Nontyphoidal Salmonella Infections Before and After the COVID-19 Outbreak: A Retrospective, Cross-sectional Study - Kundoly V. Suseela; Aiswariya Alex; Subi Das; V. Geethalakshmi (International Journal of Advanced Medical and Health Research)
Background: The number of patients with diarrheal diseases admitted to the hospital was reduced during the COVID-19 lockdown. Following the relaxation of the lockdown, admissions of nontyphoidal Salmonella (NTS) infection showed a two-fold rise compared to pre-COVID-19 years. This retrospective study aimed to detect the incidence of NTS in the pre-COVID-19 and post-COVID-19 outbreak periods, along with describing the antibiogram and comorbid conditions of the patients. Materials and Methods: Using a retrospective design, from January 2015 to December 2022, we studied stool samples for the presence of NTS. Antibiogram with ampicillin, co-trimoxazole, ceftriaxone, chloramphenicol, and ciprofloxacin were studied. The presence of comorbid conditions was noted. Results: We examined 2312 and 937 stool samples collected during the pre-COVID-19 and post-COVID-19 outbreak period, respectively. The number of samples collected during the outbreak (2020) was 273. During the pre-COVID-19 period (2015–2019), the average annual isolation rate of NTS was 5.63%. During the lockdown of 2020, the corresponding rate was 5.49%. The isolation rate showed a significant rise (11.45%) during the relaxation of the lockdown (P < 0.001). No significant change in resistance to antibiotics other than ciprofloxacin was noted in the present study. Malignancy was the leading comorbid condition (11.91%) followed by chronic liver diseases (10.31%). Conclusions: A significant rise in NTS diarrheal cases was detected following the COVID-19 outbreak. During this period, people were attending more celebrations and feasts. No significant change in antibiotic resistance was noted when comparing pre-COVID-19 and COVID-19 periods. Malignancy was the leading comorbid condition.